Treeline Ecotone Progression and Stability: Time Series Analysis of Individual Photographic Data 1973-2021 in the Swedish Scandes - Kullman, Leif; Öberg, Lisa (European Journal of Applied Sciences, 2022)
Positional and population change of the alpine treeline ecotone were studied at a site (isolated low-fell) in the Swedish Scandes. Methods included early-20th century records and subsequent re-visitations, including repeat photography, up to 2021. Substantial temperature rise (summer and winter) during the past 100 years, has left the elevational forest border virtually unchanged. However, the treelines, i.e. scattered solitary trees >2 m tall, of mountain birch (Betula pubescens ssp. czerepanovii) and Scots pine (Pinus sylvestris) have risen by maximum 70 and 65 m, respectively since the early 20th century, in contrast to inertia of Norway spruce (Picea abies). Hitherto, pine appears as the most successful species, particularly in the light of the relatively large numbers of new trees established around the elevated treeline and the proliferous regeneration in the treeline ecotone during the past few decades. Presumably, a subalpine pine belt may eventually replace the sparse birch belt in the snow-poor SE-facing slope, in accordance with regional tendencies. Climate warming has reduced the snow cover duration on the NE-facing slope, to the benefit of mountain birch. Possibly, closed birch stands will evolve here. The study mountain displays a spectrum of different local habitat types, with contrasting quantitative and qualitative responses to climate change, representative of prevailing regional treeline ecotone dynamics. Important and complex constraints to projections of treeline growth and rise, in response to alleged future climate warming, include geomorphology, herbivory and snow pack.